Business Strategy Development and Business Model RS Bakti Timah (RSBT) Groups Pangkal Pinang Under Bakti Timah Foundation (YBT) Become PT RS Bakti Timah as An Existance of Diversification Effort from PT Timah (Persero) Tbk - Wibisono, Muhammad Subuh; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
Rumah Sakit Bakti Timah groups (RSBT ) is a hospital that managed by Bakti Timah Foundation. Now, RSBT Â will become independent through forming an Inc (Incorporated) that will be called â€œPT RS Bakti Timahâ€. Concern with the stock-holdings from this PT RS Bakti Timah (99 %) by PT Timah (Persero) Tbk, and (1 %) by Bakti Timah Foundation. This research shows the internal condition of the company and external industry situation with internal and external analysis to find the root causes. In this part, the authors used some model, they are external business situation analysis (macro environment) PESTLE Analysis, Industry Analysis Porterâ€™s Five Force, Internal Analysis Resources and Capability, Business Model and Value Proposition Alignment, Business Model Need Analysis, SWOT analysis, and qualitative survey in questionnaire form and interview. From the business issues faced by RSBT groups, we got major problem thatÂ  RSBT groups has difficulty to get investment asset from investor (Bank) because its status under foundation. If RSBT groups will become independence, RSBT will get many benefit from PT Timah (Persero) Tbk Company as majority asset holder (99 %) and minority asset holder of Bakti Timah Foundation ( 1 %). From business issues that RSBT groups faced, the major caused by RSBT groupsâ€™ status under Bakti Timah Foundation until RSBT groups has difficulty to get investment asset from investor (Bank) because its status under foundation, with this independent of RSBT groups many benefit will be get for PT Timah (Persero) Tbk Company as majority asset holder (99 %) and minority asset holder of Bakti Timah Foundation ( 1 %). The result of this study we solve this problem byÂ  using Strategic Innovation and Business Model Canvas, Strategic Generic Porterâ€™s ; Corporate Strategy PT RS. Bakti TimahÂ  and Business Strategy RSBT groups, together with Business Model Canvas RSBT groups existing and Business Model Canvas RSBT groups New/proposed. From the results, we suggest to implement analysis results into practical action.Â Keywords: RSBT groups, hospital business, development strategy, Strategy Implementation, business model Canvas